Comparative Study of Soil Bacterial Communities in Pagoh Campus - Jefry, Muhammad Shah Danial; Pa'ee, Furzani (Enhanced Knowledge in Sciences and Technology, 2025)
This study conducted a comparative analysis of soil bacterial communities in two distinct locations within UTHM Pagoh Campus which are UTHM Wetland and Pagoh Residential College. The research aimed to investigate the influence of environmental factors, including pH, temperature, and moisture content, on microbial diversity and distribution. Soil samples were collected and analysed using a systematic approach, which included measurements of physical parameters, bacterial culturing, morphological examination, Gram staining, and bacterial identification. The study sought to identify the relationships between soil properties and bacterial composition, providing insights into the ecological dynamics of soil microbial communities in contrasting environments. The results showed distinct bacterial diversity where UTHM Wetland had three families of bacteria, while Pagoh Residential College had one. This is because, UTHM Wetland, characterized by acidic pH, high moisture content, and varied environmental conditions, supported a more diverse bacterial community. Families such as Enterobacteriaceae, Xanthomonadaceae, and Listeriaceae were prevalent, reflecting the wetland’s rich and dynamic habitat conducive to microbial growth. In contrast, Pagoh Residential College, with its neutral to slightly alkaline pH, dry soil conditions, and more stable environment, exhibited reduced microbial diversity, with Moraxellaceae as the dominant bacterial family. These differences underscore the role of environmental parameters and land use in shaping microbial ecosystems. The study highlights the ecological importance of wetlands as reservoirs of microbial diversity and emphasizes the impact of land conversion and reduced moisture availability on microbial communities in Pagoh residential areas. Furthermore, conservation efforts should focus on protecting and restoring wetlands to maintain their ecological balance and biodiversity. This research contributes to the broader understanding of soil microbial communities, their environmental drivers, and the need for sustainable land management practices to ensure ecosystem health and resilience.